The effect of using the smartphone blue light filter feature on tear production - Ikliluddin, Ahmad; Rahmat Saputra, Adey (Universitas Muhammadiyah Surabaya, 2024)
Smartphones today have been used to support human activities. It makes the human eye always exposed to smartphone screens that use light-emitting diodes (LEDs) that emit light with a blue electromagnetic spectrum known as blue light. The effect of blue light on human eyes is still being studied. This study aims to determine the effect of using smartphone blue light filter features on tear production. This was a quasi-experimental, pre-post study, involving 40 samples who met the inclusion and exclusion criteria. Subjects were asked to use a smartphone within 1 week without activating a blue light filter. After this, tear production was measured using the Schirmer test under topical anesthesia. Then, subjects were asked to use a smartphone again within 1 week by activating the blue light filter and being measured again using the Schirmer test under topical anesthesia. Data obtained were analyzed using SPSS 25 software. There was a statistically significant (sig=0.000) difference in Schirmer test values before and after the usage of smartphone blue light filters. Each increase in the duration of smartphone usage for one minute will decrease Schirmer test results by 0.000625 mm, and so will the multiplication. The duration of smartphone usage has a 21.6% contribution of influence on the results of the Schirmer test. In conclusion, there is an effect of using the blue light filter feature on tear production between the use of a smartphone without activating the blue light filter with the use of a smartphone that activates the blue light filter feature.